(Techno-economic Analysis of Small Scale Poultry Feed Industry) - Lukman Junaidi; Rizal Alamsyah; Mochamad Noerdin NK; Tiurlan F. Hutajulu (Balai Besar Industri Agro, 2000)
Techno-economic analysis was conducted to evaluated to evaluate the financial viability of small-scale pourly feed industry. the analysis was based on three scale of capacity. that is: 4 tones, 2 tones, and 300 kg feed per day. the result of analysis shown that the viability of the pourtry feed industry was not sensitive to changes in the investment cost. however, the viability of the poultry feed industry was very sensitive to changes in the raw materials cost and feed price.